Pendidikan Agama Kristen di Era Digital: Perspektif Progresivisme - Elsye Estrina Londo; Sugijanti Supit (PT. Giat Konseling Nusantara, 2024)
This article examines the application of progressive philosophy in Christian religious education in the digital era. By adopting a progressive approach, the methods of teaching Christian religion have undergone significant transformation from traditional methods to technology-based learning. This study identifies the challenges and opportunities arising from the digitalization of education and evaluates the effectiveness of integrating technology in enhancing student engagement and understanding. This research was conducted using the literature study method. The analysis results indicate that the progressive approach, supported by adequate technological infrastructure and professional training for educators, can improve the quality of Christian religious education, making it more adaptive to the needs of students in the digital era.